2021
DOI: 10.3390/v13010060
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Phage Therapy against Pandrug-Resistant Achromobacter xylosoxidans in a 12-Year-Old Lung-Transplanted Cystic Fibrosis Patient

Abstract: Bacteriophages are a promising therapeutic strategy among cystic fibrosis and lung-transplanted patients, considering the high frequency of colonization/infection caused by pandrug-resistant bacteria. However, little clinical data are available regarding the use of phages for infections with Achromobacter xylosoxidans. A 12-year-old lung-transplanted cystic fibrosis patient received two rounds of phage therapy because of persistent lung infection with pandrug-resistant A. xylosoxidans. Clinical tolerance was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 30 publications
(36 reference statements)
0
59
0
4
Order By: Relevance
“…We al-so showed that three out of five phages isolated individually from the same sample virome with plaque assay are ineffective of lysis in liquid media or outcompeted by phages from the same virome. This has to be considered when deciding if the single isolated phages are good potential candidates for treatment in phage therapy or biocontrol [17,29,[68][69][70]. Furthermore, our analysis highlighted how much longread sequencing data improves the assembly of viral metagenomes as we saw an increase of 5.64% in the proportion of complete phage genomes from long-read assembly compared to short-read-only assemblies (p-value < 0.0001, Figure 2).…”
Section: Discussionmentioning
confidence: 84%
“…We al-so showed that three out of five phages isolated individually from the same sample virome with plaque assay are ineffective of lysis in liquid media or outcompeted by phages from the same virome. This has to be considered when deciding if the single isolated phages are good potential candidates for treatment in phage therapy or biocontrol [17,29,[68][69][70]. Furthermore, our analysis highlighted how much longread sequencing data improves the assembly of viral metagenomes as we saw an increase of 5.64% in the proportion of complete phage genomes from long-read assembly compared to short-read-only assemblies (p-value < 0.0001, Figure 2).…”
Section: Discussionmentioning
confidence: 84%
“…We also showed that three out of five phages isolated individually from the same sample virome using the plaque assay were ineffective in terms of lysis in liquid media or outcompeted by phages from the same virome. This has to be considered when deciding if single isolated phages are good potential candidates for treatment in phage therapy or biocontrol [ 17 , 29 , 70 , 71 , 72 ]. Furthermore, our analysis highlighted how much long-read sequencing data improve the assembly of viral metagenomes, as we saw an increase of 5.64% in the proportion of complete phage genomes from long-read assembly compared to short-read-only assemblies ( p -value < 0.0001, Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This principle is well established in modern phage therapy, since it is identical to the one that has been used to guide the successful development of chemical antimicrobial and antiviral cocktails since at least the late 1980s [ 232 , 233 ]. Consequently, the field is rife with phage therapy trials employing polyphage cocktails, including several successful human trials, with authors consistently reporting the predictable superiority of these cocktails over monophage therapy [ 135 , 172 , 182 , 187 , 193 , 195 , 196 , 213 , 234 , 235 , 236 , 237 , 238 ]. Despite the criticisms levelled against temperate phages by a number of authors, polyphage cocktails that combine temperate phages with more virulent types also appear to be highly effective [ 165 , 172 , 187 ].…”
Section: Bacteriophage Therapymentioning
confidence: 99%